The Influence of Packaging Attributes on Consumer Buying Pattern in Food Packaging: A Case of Kathmandu Valley - Shrestha, Deepa Kumari (Nepalese Journal of Business, 2024)
This study examines the influence of packaging attributes on consumer buying behavior in Kathmandu Valley. Consumer buying behavior is the dependent variable. The selected independent variables are packaging color, packaging material, graphics, information and innovation. The primary sources of data is used to assess the opinions of respondents regarding the packaging color, packaging material, graphics, information and innovation. The study is based on the primary data of 127 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the influence of packaging attributes on consumer buying pattern in food packaging: A case of Kathmandu Valley. The study showed a positive impact of packaging color on consumer buying behavior. It indicates that attractive packaging color leads to change in consumer buying behavior. Likewise, packaging material is positively correlated to consumer buying behavior. It indicates that quality packaging material stimulates the consumer buying behavior. Similarly, graphics is positively correlated to consumer buying behavior. It indicates that better graphics of products change the consumer buying behavior. Further, information is also positively related to the consumer buying behavior. It indicates that reliable information of the products leads to change in consumer buying behavior. Moreover, innovation is positively correlated to consumer buying behavior. It shows that the innovative packaging communicates the brands and commitment to quality towards consumer buying behavior.